PENGARUH PENDAPATAN, USIA, DAN JANGKA WAKTU KREDIT TERHADAP JUMLAH KREDIT PENSIUN PADA PT BANK TABUNGAN PENSIUNAN NEGARA CABANG SURAKARTA - Lisa Muri Hartatie, Dewi Saptantinah Puji Astuti & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The objective of the research are (1) to analyses effect income debtor to amount of pension credit, (2) to analyses effect age to amount of pension credit, (3) to analyses effect credit period to amount of pension credit, (4) to describe the authorization procedure in granting pension credit at Bank Tabungan Pensiunan Negara (BTPN) branch in Surakarta. This research using samples of 100 debtors of pension credit at Bank Tabungan Pensiunan Negara (BTPN) branch in Surakarta. Data collecting using questionnaire. Data were analyzed using multiple linear regression analysis. The conclusion from the results of testing each hypothesis shows that (1) Income debtor has positive and significant effect to amount of pension credit meaning hypothesis 1 accepted (2) age debtors has negative and no significant effect to amount of pension credit, meaning hypothesis 2 rejected (3) credit period has positive and significant effect to amount of pension credit, meaning hypothesis 3 accepted. (4) The authorization procedure in granting pension credit at Bank Tabungan Pensiunan Negara (BTPN) branch in Surakarta has been conducted in accordance with the applicable provisions of BTPN bank, indicated by the separation of duties of employees who perform duties in accordance with their responsibilities.Keywords: revenue, age, credit period, amount of pension credit